Investigation on common errors made by audiology students during clinical training - Mohd Puzi, Nur Ain Fathanah; Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah (IIUM Press, 2017)
Objectives/Research Problem: Simulated Learning Environment (SLE) is the current educational pedagogy that has been applied in audiology. It has been suggested that SLE should include as much as possible formative feedback component to ensure any mistakes made by the students in the SLE training can become a form of reflective learning. This study aims to identify the common errors made by the audiology students in the clinic through questionnaire survey. Materials and Method: A new set of questionnaire has been developed by reviewing IIUM clinic protocol and from qualitative opinion given by two audiology instructors. The questionnaire has been validated by two experts in language to improve the overall readability of the questionnaire. In future phase, the questionnaire will be validated by two experts (familiar with audiology) to check the relevancy of each of the item through statistical evaluation. The actual survey will be carried among 10 audiology preceptors (n=10) from Universiti Sains Malaysia (USM), Universiti Kebangsaan Malaysia (UKM) and International Islamic University Malaysia (IIUM). Results and Discussion: The common errors will be ranked from the least to the most common based on the answers from the questionnaire. Conclusion: With the typical errors obtained from this study, a comprehensive feedback module can be included for future novel audiology SLE training.